2014
DOI: 10.1016/j.juro.2013.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity Associated with Primary High Intensity Focused Ultrasound and Redo High Intensity Focused Ultrasound for Localized Prostate Cancer

Abstract: Redo high intensity focused ultrasound is associated with an increase in urinary side effects but sexual side effects do not appear to be significantly increased. The number of adverse events seems to be equivalent after first and redo treatments. Meticulous patient selection is of paramount importance when selecting men for redo high intensity focused ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…When comparing our results to reported studies in the literature, the only comparable paper is that of Berge et al This analysis, from our own HEAT registry of whole‐gland HIFU cases, in men undergoing redo HIFU suggested equivalence between the rate of adverse events after first and redo treatments, and reported worse urinary function in terms of pad and leak status, both after initial HIFU treatment, and a decline in leak‐free status after redo whole‐gland HIFU, differences not observed in the present focal outcomes study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…When comparing our results to reported studies in the literature, the only comparable paper is that of Berge et al This analysis, from our own HEAT registry of whole‐gland HIFU cases, in men undergoing redo HIFU suggested equivalence between the rate of adverse events after first and redo treatments, and reported worse urinary function in terms of pad and leak status, both after initial HIFU treatment, and a decline in leak‐free status after redo whole‐gland HIFU, differences not observed in the present focal outcomes study.…”
Section: Discussionsupporting
confidence: 76%
“…We have previously published functional outcomes from a single session of focal HIFU and focal cryotherapy, and also the functional outcomes of second whole‐gland HIFU treatment, demonstrating minor detrimental effects . There is a paucity of data, however, on the effects of a second focal HIFU treatment on functional outcomes . We present an analysis based on data from the HEAT registry, assessing change in urinary function and erectile function (EF) measures in men who underwent a second focal HIFU procedure.…”
Section: Introductionmentioning
confidence: 99%
“…As a minimally-invasive, ambulatory therapy that requires no incisions and the unique ability to successfully repeat it in most patients, if necessary, may have some advantages over other therapies for some patients. Indeed, we have previously reported that redo-HIFU following whole-gland HIFU is associated with a small deterioration of urinary function but no deterioration in erectile function [31]. As a result, those patients, physicians, and healthcare services looking at alternative treatment strategies to radical wholegland therapy that can be delivered with low cost, conferring favourable urinary functional outcomes and acceptable medium-term cancer control, might consider whole-gland HIFU.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen studies were identified and a total of 5695 patients treated from 43.6 to 88 years old were reported (Table 2 ). [ 3 20 ] The majority of patients had stage T1-T3 disease; 10 studies included cases with T3. The mean or median pre-HIFU PSA was 5 to 10 ng/mL.…”
Section: Resultsmentioning
confidence: 99%